Bilingualism In African And Middle East Communities In New York - Helmy, M. Ridwan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2018)
This paper is aimed at arguing chapter 9, 10 and 11 of the book â€œBilingual Community Education and Multilingualism: Beyond a Heritage Language in a Global City by Ofelia Garcia, ZeenaZakharia, and BaharOtcuâ€, published in 2013. Arguing those three chapters, the reviewer explore the issue deeply, give arguments on the strengths and weaknesses of their analysis,and finally, the reviewer takes a conclusion.Examining these chapters, the reviewer identified that in chapter 9, the author showed the issue interestingly. Also, the authors were very good at presenting the issue of heritage language initiatives.It is obvious also to see that the way the writers presented the certain phrases add an attractiveness to read this chapter.However, it is hard not to argue that the authors have some constraints to explore deeply on specific languages of Africa. Since there are various languages in African society. In Chapter 10, the reviewer would say that the authors have shown their expertise perfectly, since they addressed the issue in a very comprehensive way on how and why the Iranian community in New York engage in bilingual community education, In Chapter 11, the authors showed their strength of the analysis. Also, the strength of this chapter is on the way the authors show their good knowledge politically by explaining what happened in the mid- 2000s in U.S. policy, and the implication of this policy. In chapter 10 and 11, the reviewers didnâ€™t identify the weaknesses of the author.